2003
DOI: 10.1023/b:brea.0000004371.48757.19
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Cutaneous Tumor Lesions in Patients Intratumorally Injected with a Recombinant Single-chain Antibody-toxin Targeted to ErbB2/HER2

Abstract: ScFv(FRP5)-ETA is a recombinant single-chain antibody-toxin with binding specificity for ErbB2/HER2. Previously potent antitumoral activity of the molecule against ErbB2 overexpressing tumor cells was demonstrated in vitro and in animal models. Here we report on the first application of scFv(FRP5)-ETA in human cancer patients summarizing case reports collected in four different clinical centers. Eleven patients suffering from metastatic breast and colorectal cancers and from malignant melanoma were treated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 27 publications
0
55
0
Order By: Relevance
“…The treatment was given by intra-tumoral injection. Out of 11 patients, 4 showed complete remission and 3 showed partial remissions [56]. Another phase I trial was reported in 2005.…”
Section: Scfv(frp5)-etamentioning
confidence: 99%
“…The treatment was given by intra-tumoral injection. Out of 11 patients, 4 showed complete remission and 3 showed partial remissions [56]. Another phase I trial was reported in 2005.…”
Section: Scfv(frp5)-etamentioning
confidence: 99%
“…Gene amplification and ErbB2 overexpression have been observed in many human tumors, including breast and ovarian cancers, nonsmall cell lung cancers, and cancers of the head and neck, and have been linked with cancer development and progression (3)(4)(5). With humanized mAb Herceptin, an ErbB2-specific reagent is in clinical use for immunotherapy of breast cancer (6), and alternative Abbased therapeutics are under development (7,8).…”
mentioning
confidence: 99%
“…Anti-Her2/neu immunotoxins containing PE have shown potent antitumor activity in animal models (23,33) but resulted in unexpected hepatotoxicity in all patients likely due to the normal presence of Her2/neu on hepatocytes (34,35). Studies by Onda and colleagues found that overall positive charge on anti-Tac(Fv) PE38 immunotoxin contributed to nonspecific binding to liver cells and resulted in dose-limiting liver toxicity (36,37).…”
Section: Discussionmentioning
confidence: 99%